The effects of berberine on depressive symptoms: a systematic review and meta-analysis of preclinical studies - Li, Xiaona; Lu, Mei; Wang, Xinkun; Wu, Di; Chen, Yongmei; Tao, Ming; Gou, Dengqun; Yang, Runyu; Zhou, Jiamei (Frontiers in Psychiatry, 2025)
IntroductionDespite preclinical evidence for berberine's antidepressant potential, its pharmacological effects remain controversial.This study therefore systematically reviews animal research to clarify its mechanisms and support future clinical trials.MethodsWe searched PubMed, Embase, Web of Science, Cochrane Library, and OVID for studies on berberine in depression models up to March 20, 2025. Analysis used STATA 15.0 and Review Manager 5.4, with study quality assessed via SYRCLE's risk of bias tool.ResultsThe meta-analysis included 18 studies (338animals). Overall, berberine significantly reduced depression-like behaviors in animal models.Specifically, BBR increased total locomotor activity in the open field test (SMD=2.79, 95% CI: 1.55, 4.02) and time spent in the center zone (SMD=2.49, 95% CI:1.61, 3.37), reduced immobility time in both the forced swim test and tail suspension test (SMD =-4.42, 95% CI:-5.77,-3.07; SMD=-4.46, 95% CI:-6.21, -2.71), increased sucrose intake in the sucrose preference test (SMD = 3.72, 95% CI: 2.37, 5.07), and reduced feeding latency in the novelty-suppressed feeding test (SMD=-5.72, 95% CI:-7.63, -3.82). However, BBR did not significantly alter the number of square crossings (SMD=1.36, 95%CI:-0.07 , 2.79) or rearing frequency (SMD=1.66, 95% CI: -0.29, 3.61) in the open field test. BBR also increased the levels of body weight, brain-derived neurotrophic factor, dopamine, serotonin, and norepinephrine,while reducing the levels of pro-inflammatory cytokines including TNF-α, IL-1β, and IL-6.DiscussionPreclinical studies suggest that berberine may represent a promising therapeutic agent for the treatment of depressive disorders. Its antidepressant effects appear to be closely associated with the modulation of neurotransmitter levels,reduction of oxidative stress, and inhibition of inflammatory responses.However, methodological limitations may constrain these findings. Larger, more rigorous preclinical studies are needed for confirmation.Systematic review registrationhttps://inplasy.com/inplasy-2025-6-0002, identifier INPLASY202560002.